P-48 Learning together: a training needs analysis to promote inclusion of hospice staff in the development of an educational strategy. (20th March 2022) - Stanley, Sarah; Shaw, Emma; Bonwick, Helen
Abstract : Background: In order for healthcare professionals to feel confident in their role it is important that their educational needs are met. A training needs analysis is essential in establishing the continuing professional development of a health care workforce. 1 Training needs analysis looks to identify gaps in knowledge and skill for an individual or organisation, allowing the trainer and the person/s requesting training to develop an educational plan together. 2 Aims: To improve confidence amongst staff by identifying gaps in knowledge and forming an educational plan to meet their needs. Methods: An online and paper based questionnaire was developed, giving hospice staff the opportunity to be involved in developing their own plan of education. Consisting of 35 questions, the survey asked individuals to self-assess different aspects of their own work. For each topic respondents were asked to rate how important they felt the topic was to their role and how confident they felt in this area. A final question provided the opportunity for respondents to give free text responses on their hopes and requirements for future education. Results: We received 38 responses from different healthcare professionals working in the hospice. Results of the questionnaire identified gaps in knowledge amongst different disciplines, providing us with the essential information needed to develop an educational strategy to meet the needs of our staff. Feedback from staff has been positive as they have reported a feeling of inclusion and an appreciation of having their voices heard. Conclusion: Developing a training needs analysis to identify the educational needs of hospice staff has proven to be successful, positively engaging staff in order to develop an inclusive plan of education. References: Gould D, Kelly D and White I. Training needs analysis: an evaluation framework. Nurs Stand 2004;18 :33–36. Barbazette J. Training needs assessment: methods, tools and techniques. San Francisco, CA: John Wiley & Sons, 2006.